2020
DOI: 10.4187/respcare.07437
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Status Is Associated With Successful Discharge Home in Survivors of Critical Illness

Abstract: BACKGROUND: Survivors of prolonged ICU admissions are bedridden and immobilized for an extended period of time. These patients often are discharged to long-term acute care hospitals (LTACHs) for continued medical care and rehabilitation. Early ambulation has been associated with improved functional outcomes and lower readmission rates in hospitalized patients. The aim of this study was to determine the association between ambulatory status and discharge disposition in survivors of prolonged ICU stays who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…He recovered successfully and was able to ambulate independently upon discharge, likely as a result of daily aggressive mobility-focused rehabilitation. Our prior study has shown that mobility-based rehabilitation is associated with higher rates of survivors of critical illness being discharged home [ 9 ]. He was discharged home fully independent, without oxygen supplementation, on hospital day 63.…”
Section: Discussionmentioning
confidence: 99%
“…He recovered successfully and was able to ambulate independently upon discharge, likely as a result of daily aggressive mobility-focused rehabilitation. Our prior study has shown that mobility-based rehabilitation is associated with higher rates of survivors of critical illness being discharged home [ 9 ]. He was discharged home fully independent, without oxygen supplementation, on hospital day 63.…”
Section: Discussionmentioning
confidence: 99%
“…Pelo que, há necessidade de elaborar e implementar programas de treino de atividades de vida diárias visando a adaptação às limitações da mobilidade e à maximização da autonomia e da qualidade de vida e promover a mobilidade, a acessibilidade deambular e a participação social. Tendo-se verificado que é um fator determinante no regresso ao domicílio (Tran, et al 2020) e que é necessário a elaboração de mais programas de reabilitação para reduzir os riscos (Tempera, et al 2013).…”
Section: Discussionunclassified
“…foram para instalações de reabilitação de agudos, 70 tinham enfermagem domiciliária, 139 foram readmitidos na UCI e 13 morreram. Dos 285, 74 deambularam durante a fisioterapia dos quais 24 foram para casa, enquanto que 211 nunca deambularam e apenas 14 foram para casa.No estudo(Tran, et al, 2020) dos 285 participantes, 68% foram transferidos de UCI. A média de permanência nas UCI e em hospitais de cuidados agudos de longa duração foi de 25.5 e de 34 dias, respetivamente.…”
unclassified